The Influence of Teaching Approach on Students’ Conceptual Learning in Physics - Bigozzi, Lucia; Tarchi, Christian; Fiorentini, Carlo; Falsini, Paola; Stefanelli, Federica (Frontiers in Psychology, 2018)
Physics is fundamental to secure future needs for scientific and technological competence (Angell et al., 2004; Drury & Allen, 2002), but many countries experience a drop in students' performances in international assessments (OECD, 2018), as well as in rates of enrolment in undergraduate programs in scientific disciplines (STEM). Socio-constructivist theories have produced a reforming movement in several educational systems, in particular in the area of sciences, but teacher often consider them an idealistic view of education and do not consider themselves metacognitively competent enough to foster thinking in the classroom (Shakhman, 2008). In this study we investigated the efficacy of different teaching methods on high school students' conceptual knowledge of physics, after the effect of science-related beliefs and critical thinking skills was controlled. We adopted a mixed-method with sequential design, in which quantitative and qualitative data flow are inter-mixed. In specific, we interviewed four high school physics teachers to identify teaching approaches (qualitative approach) and compared them in terms of efficacy on students' performances (quantitative approach). Four teachers and 77 10th grade students participated. Teachers were interviewed during the school years, and asked questions about their teaching experience, their teaching approach (Kang & Wallace, 2004; Stipek, 2004) and their epistemic beliefs (Abd-El-Khalick, 1998; Tsai, 2002). Students performances in Science-related beliefs (Conley et al., 2004), critical thinking (Cornell Critical Thinking Test Level X, Millman et al., 2005), and conceptual knowledge in physics (The Force and Motion Conceptual Evaluation, Ramlo, 2002) were evaluated twice, at the beginning and at the end of the school year. The independent-sample t-tests on pretest variables did not reveal any statistically significant difference between groups. Results from the complex samples GLM revealed statistically significant differences on posttest scores in conceptual knowledge in physics, after the effect of covariates was controlled. Overall, the study contributes to our understanding on current teaching practices in school, and their effect on students' conceptual understanding of physics concepts.